2000
DOI: 10.1097/00000478-200003000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Renal Sinus Involvement in Renal Cell Carcinomas

Abstract: The renal sinus is the fatty compartment located within the confines of the kidney not delineated from the renal cortex by a fibrous capsule. Because it contains numerous veins and lymphatics, invasion into this compartment may permit dissemination of a tumor otherwise regarded as renal-limited. Thirty-one consecutive renal carcinomas were studied: 22 clear cell renal cell carcinomas (3 multilocular cystic renal cell carcinomas), 4 chromophobe renal carcinomas, and 5 papillary renal carcinomas. The entire inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(57 citation statements)
references
References 33 publications
2
52
0
2
Order By: Relevance
“…The sampling in this retrospective series, although consistent with UK practice, was limited compared with that recommended by Bonsib et al [13], who found that complete sampling of the interface between the tumour and the renal sinus identified vascular invasion in six of 16 RCCs with no RVI, more than twice the incidence found in the present study. A more detailed histological examination of the resection specimen would be expected to identify more cases with MVI; histopathologists will need to respond to this challenge.…”
Section: Discussionsupporting
confidence: 84%
“…The sampling in this retrospective series, although consistent with UK practice, was limited compared with that recommended by Bonsib et al [13], who found that complete sampling of the interface between the tumour and the renal sinus identified vascular invasion in six of 16 RCCs with no RVI, more than twice the incidence found in the present study. A more detailed histological examination of the resection specimen would be expected to identify more cases with MVI; histopathologists will need to respond to this challenge.…”
Section: Discussionsupporting
confidence: 84%
“…The identification of separate tumor nodules in the perinephric fat by gross examination is diagnostic of pT3 disease. Under the 2002 AJCC system, extension into the renal sinus fat is also regarded as extra renal extension [8] (pT3a). In one study that specifically addressed extension into the sinus fat, this was a vastly more common route of perinephric soft tissue extension [9].…”
Section: Gross Descriptionmentioning
confidence: 99%
“…The rationale for including renal sinus involvement in pT3 is the evidence that renal CC preferentially extends beyond the kidney by invasion of the renal sinus. [2][3][4] Recently published outcome data from the Mayo Clinic have validated this revision, with the demonstration that the prognosis for sinus invasion is very poor, with a 5-year survival of only 26%. 5 Renal sinus invasion is usually associated with invasion of renal sinus veins, accounting for the predilection of clear cell renal CC to metastasize to lung, liver, bone and brain.…”
mentioning
confidence: 98%